Methods of access for people with intellectual disabilities to public education curricula and the factors affecting them from the point of view of teachers in Al-Jouf region - Alshammari, May Farzal; Albulayhid, Maha Saud (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the methods of access of people with intellectual disabilities to public education curricula and the factors affecting them from the point of view of teachers in the Al-Jouf region, and also aimed to verify the existence of statistically significant differences in access methods and the factors affecting them that may be attributed to the difference in gender variable, years of experience, and educational qualification; The study followed the descriptive approach, and the questionnaire was used as a research tool, the study sample included 119 (male and female teachers in Al-Jouf region during the third semester of the academic year 1444 AH, The study reached that teachers reported on the methods of access of students with intellectual disabilities to the general education curriculum with regard to addition, deletion and modification to a high degree, and the methods of access for those were arranged according to the following: deletion, modification, and addition. The study also showed a number of factors affecting the methods of access of those students in descending order according to the most influential according to the following: factors related to the teacher, factors related to students, factors related to school systems, and the results showed that there are statistically significant differences between the responses of teachers about the three methods (addition, deletion and modification), and also about the previous factors affecting the methods of access is due to the difference in the gender variable in favor of female teachers, and it was noted that there were no statistically significant differences between the average responses of male and female teachers due to the difference in the variable of years of experience and educational qualification.